Optimization of nitrogen and carbon requirements and culture incubation time for maximum Poly-ß-hydroxybutyrate (PHB) production by Bacillus sp. Jl 47 isolate from shrimp pond sediments - Bautista, Norwell Brian Chavez ([Miag-ao, Iloilo] University of the Philippines Visayas, 2015)
Poly-ß-hydroxybutyrate (PHB) is a biopolymer that has been previously demonstrated to improve immune response and growth in some fish and shrimp species and has been considered as an alternative for the use of synthetic chemicals, such as antibiotics, in aquaculture. PHB can be produced by microorganisms, among which is, Bacillus sp. LJ 47, ioslated from shrimp pond sediments. PHB-rich probiotic bacteria may then be used to supplement diets for shrimps aquaculture to induce both disease-resistance and growth in cultured shrimp. The specific objectives of this study are to optimize nitrogen and carbon requirements and culture incubation time for the culture of bacillus sp. JL47 to produce maximum PHB. The study tested different nitrogen and carbon sources. After the preferred sources have been identified, their respective optimum levels and the optimum level for culture incubation time were determined using response surface methodology (RSM). Bacillus sp JL47 accumulates the most PHB when it is grown using maltose s main carbon source and yeast extract in equal quantity with peptone as main nitrogen source. A simultaneous evaluation via RSM, of % maltose (w/v), % yeast extract + peptone (w/v) and culture incubation time, showed that Bacillus sp.JL47 accumulates the most PHB when grown in 2.2% maltose, 0.8% yeast extract + peptone (pH=7, bacterial inoculum, OD=1; temperature, 30 C and minimal media composition, held constant in all experiemnts). Moreover, it was found that PHB production is unaffected by culture incubation time from 48 to 96 hours. At the predicted optimum, the carbon-to-nitrogen ratio is 3. Bacillus sp. JL47 can accumulate PHB at least 46% on cell dry weight using the optimized carbon and nitrogen requirements.
Special Problem (M. Chemistry) -- Miagao, Iloilo : University of the Philippines Visayas, December 2015.